KEBIJAKAN RESTRUKTURISASI KREDIT PEMILIKAN RUMAH PADA SAAT PANDEMI COVID-19 DI PT BANK TABUNGAN NEGARA TBK KC MEDAN - jes, jesica (LPPM Universitas Malikussaleh, 2025)
A home is a place to raise a family. The Covid-19 outbreak has had an impact on unstable inflation, resulting in a decline in the development of the property sector in Medan. Many debtors are unable to continue their obligations to pay housing loans. The research method used is normative juridical and empirical juridical, conducting interviews with sources. The purpose of the study is to analyze the policy of restructuring home ownership loans during the Covid-19 pandemic, analyze the obstacles to implementing the postponement of home ownership loan payments and analyze efforts to overcome obstacles to providing home ownership loans during Covid-19 at PT Bank Tabungan Negara. The results of this research indicate that bank regulations in providing credit are based on Article 1 paragraph (2) of Law No. 10 of 1998, Article 2 Paragraph (2) of the Regulation of the Financial Services Authority of the Republic of Indonesia Number 48/POJK.03/2020 providing restructuring. Obstacles in implementing the restructuring policy for mortgages at PT Bank Tabungan Negara Tbk KC Medan include subsidized mortgage debtors because the debtor received a salary cut, family members died due to corona, and Bank management does not yet have detailed and standard technical instructions for implementation. The efforts made by the bank to collect debts peacefully from debtors, hold discussions and auction efforts are carried out by KPKNL (State Service and Auction Office).